A Model of Plate Bending at the Transition Zone From Subduction to Collision in Northernmost Manila Trench. Issue 18 (19th September 2022) - Zhang, Jiangyang; Sun, Zhen; Yang, Hongfeng; Zhang, Fan
Abstract: It is not rare to observe subduction zones transferring into collision zones. However, it is poorly understood the lateral variation in flexural deformation. Constrained by newly published seismic reflection data, we investigate the mechanical behavior of lithosphere from oceanic subduction to collision at the northern Manila trench using the 3‐D flexural modeling. Results show that both plate rigidity and the loadings increase from the Manila subduction zone to the Taiwan orogenic belt. In order to fit all observations, an upward loading was required at the transition zone from subduction to collision, which may be related to the variation of buoyancy due to density contrast of plate from south to north. The resultant maximum bending stress is consistent with the concentrated seismic activity at the southwest of Taiwan, suggesting that huge loading from the orogeny and lateral density change of subducting plate play important roles in bending and seismicity. Plain Language Summary: Converge of two plates forms the subduction zone and collision zone, causing great bending of lithosphere. Faulting and earthquakes may be induced by plate bending when the deformation exceeds strength limit of lithosphere. Here, the flexural of the subducting plate along the northernmost Manila trench has been simulated by a 3D model. Results show that from subduction to collision, both surface loading coming from mountain belt and buoyancy difference between oceanic and continental plate play critical roles in plate bending. The results also reveal that the buoyancy difference due to density contrast between the oceanic and continental plate may generate an upward loading at the transition zone from subduction to collision. Concentrated intraplate seismic activity at depth of ∼50 km is consistent with the maximum value of simulated bending stress and we finally proposed a concept model to illustrate plate bending and seismicity at the transition from subduction to collision. Key Points: Plate bending at the transition from the Manila subduction zone to the Taiwan collision zone was simulated by a 3‐D flexural model High value of plate bending stress in simulation is consistent with the concentrated seismic activity at southwest of the Taiwan We proposed a concept model to illustrate plate bending and seismicity at the transition from subduction to collision